Problems of Accession of the Balkan Countries to the European Union (6th International Balkan Summer School Balkans and Global Politics Proceedings, 2024)
The article deals with a set of problems that make it possible to place the Balkans in the context of pan-European development, primarily the so-called unlimited expansion of the European Union, the entry into which is the goal of the post-socialist countries of the Balkan region/South-Eastern Europe. Currently, Bulgaria, Romania, as well as the post-Yugoslav states of Slovenia and Croatia have become full members of the EU; Serbia, Bosnia and Herzegovina, Montenegro, North Macedonia, and Albania are still in different stages of the process of joining the European Union. Accession to the EU is the logical conclusion of the social, political, economic, and legal transformation of the Balkan countries, in which both they and the EU as a whole and its individual states are interested for reasons of geopolitics and geo-economics. However, the accession to Europe (or return to Europe) of the Balkan states, whose history is associated with an authoritarian socialist past, includes not only the reform of the economic and political systems, but also a change in value orientations. Nevertheless, while in the founding countries of the EU a Western European corporate civic identity is being formed, in the countries of former Eastern Europe and the Balkan region the basis of public consciousness is still largely defined by ethnic identity.